Independent non-executive directors strategic role - some evidence from Malaysia - Annuar, Hairul Azlan (Emerald Group Publishing, 2014)
Purpose – The overall purpose of the research presented is to ascertain whether independent non-executive directors (INEDs) in Malaysian publicly listed companies (PLCs) are involved in corporate strategy. Design/methodology/approach – A qualitative approach, consisting of a series of interviews with board members, was chosen. The sampling frame was made as large as possible and, for the purpose of this study, consisted of board members who sit on PLCs of the main board and Malaysian-owned. Findings – The findings reveal that INEDs in Malaysia may display the same types of involvement in the formulation phase as their counterparts in UK, which McNulty and Pettigrew (1999) categorised as taking strategic decisions, shaping strategic decisions and shaping the context, conduct and content of strategy. The findings also show that the three phases of strategy are linked and that INEDs’ behaviour during evaluation may be moderated by the strategy’s success or failure and by their involvement in the earlier phases. Research limitations/implications – This research utilised interviews. Generalisations may be an issue when interviews are used as the method of inquiry. Also, the sample is not random, as access to many directors depended on recommendations. In addition, respondents were consciously selected to obtain various board positions that include independent and non-independent directors. Practical implications – Findings from this research suggest that the involvement of INEDs in different phases of corporate strategy is an indication that INEDs are no longer focusing much on policing the management. Although control is still a major issue on the board agenda, their strategic involvement may suggest that INEDs are adequately meeting their responsibilities of providing long-term direction to their companies and also suggests that INEDs are in a position to support the Chair effectively. Their active involvement is likely to result in successful strategic formalization and conclusion. Originality/value – There is a lack of work on studying barriers to INEDs’ effectiveness in developing countries, whereby previous work and literature review were predominantly based upon the experience of Western economies.